What Kind of Brexit do Voters want? Lessons from the Citizens' Assembly on Brexit. Issue 4 (7th June 2018) - Renwick, Alan; Allan, Sarah; Jennings, Will; Mckee, Rebecca; Russell, Meg; Smith, Graham
Abstract: The Citizens' Assembly on Brexit was a major exercise in deliberative public engagement conducted in autumn 2017. It brought together fifty randomly selected members of the public for two carefully structured weekends of listening, learning, reflecting and discussing. Assembly members considered what post‐Brexit arrangements the UK should pursue, focusing on trade and migration. On trade, most members wanted the UK to pursue a bespoke arrangement with the EU and rejected the option of leaving the EU with no deal. On migration, most wanted the UK to maintain free movement of labour while using already available policy levers to reduce immigration numbers. These findings provide unique insight into informed public opinion on vital, pressing policy questions. The Assembly also illustrates the valuable role that such deliberative exercises could play in UK democracy. We suggest they could be particularly helpful for unlocking progress on issues such as the future of social care, that are often felt to be 'too difficult' to handle.